Luminescence of X-ray induced radiation defects in modified lithium orthosilicate pebbles with additions of titanium dioxide - Cipa, Janis; Kizane, Gunta; Supe, Arnis; Zolotarjovs, Aleksejs; Zarins, Arturs; Baumane, Larisa (Lithuanian Academy of Sciences Publishers, 2017)
Modified lithium orthosilicate (Li4SiO4) pebbles with additions of titanium dioxide (TiO2) are designed as a possible tritium breeder ceramic for the helium cooled pebble bed (HCPB) test blanket module. Additions of TiO2 were chosen to enhance mechanical properties of the tritium breeder pebbles. The formation of radiation defects (RD) in the modified Li4SiO4 pebbles with a different content of TiO2 was studied by X-ray induced luminescence (XRL) technique. After XRL measurements the accumulated RD were also analyzed by thermally stimulated luminescence (TSL) and electron spin resonance (ESR) spectrometry. XRL spectra consist of several bands with maxima at around 430, 490, 690, 700 and 800 nm. The XRL band with a peak at 490 nm could be associated with intrinsic defects in Li4SiO4 matrix whereas all the other maxima at lower photon energies are the result of the addition of TiO2.
The authors greatly acknowledge the technical and experimental support of O. Leys, M. H. H. Kolb, and R. Knitter (Karlsruhe Institute of Technology, Germany). The work is performed in the frames of the University of Latvia financed project No. Y9-B044-ZF-N-300, “Nano, Quantum Technologies, and Innovative Materials for Economics”.
Keywords: lithium orthosilicate; titanium dioxide; X-ray induced luminescence; XRL; thermally stimulated luminescence; TSL; electron spin resonance; ESR; Research Subject Categories::NATURAL SCIENCES:Physics